Application of the workload indicators of staffing need (WISN) to assess dietetic workforce needs in South African central and tertiary public hospitals - Vertharani Nolene Naicker; Jane W. Muchiri; Keshan Naidoo; Modiehi Heather Legodi (Scientific Reports)
Abstract South Africa faces both under- and over-nutrition, highlighting the need for prioritizing nutrition services. Registered dietitians are crucial for delivering appropriate and quality nutrition services. Consequently, this case study employs the World Health Organization evidence-based Workload Indicators of Staffing Need to ascertain the requisite dietetic workforce needed at central and tertiary public hospitals in South Africa. Head dietitians from 21 of 22 central and tertiary public hospitals participated in an online survey to provide data and consensus on workload components and activity standards via Delphi technique. Data were analyzed using the World Health Organisation Workload Indicators of Staffing Need software. Dietetic staffing needs were determined based on the difference between existing and required numbers of dietitians. WISN ratio was used as a metric to gauge dietitians’ workload pressure. Majority (95%) of hospitals experienced dietetic staff shortages and few (14%) had requisite staff to cover basic health services. Majority (76%) exhibited a WISN ratio below 0.5, indicating fullfilment of less than 50% of staff requirements. Based on the Workload Indicators of Staffing Need, dietitians in South African central and tertiary public hospitals experience high workload pressures due to extreme understaffing. The results can guide future profession workforce planning to facilitate enhanced nutrition outcomes in South Africa.